Safety and Immunogenicity of a novel three-dose recombinant nanoparticle rabies G protein vaccine administered as simulated post exposure immunization: A randomized, comparator controlled, multicenter, phase III clinical study. Issue 11 (2nd November 2021) - H S, Ravish; Khobragade, Akash; Satapathy, Durga; Gupta, Monica; Kumar, Surendra; Bhomia, Vinay; V, Ramasubramanian; Desai, Maharshi; Agrawal, Ashok Dilipkumar
ABSTRACT: Background: Rabies vaccines are lifesaving in human post animal exposure. However, the compliance to the complete course of vaccine is found to be only 60%. Hence, there is a need for safe and immunogenic, shorter course vaccine that can enhance the compliance and effectively prevent the disease. Objectives: To establish a noninferiority of a novel three-dose recombinant rabies G protein vaccine to be administered as simulated postexposure prophylaxis when compared to five-dose WHO prequalified vaccine for better safety and immunogenicity. Methods: A multi-centric, open label, assessor blind, center-specific block randomized, parallel design, phase III clinical study was conducted among 800 subjects. The eligible subjects were randomized in 2:1 ratio for recombinant rabies G protein vaccine and the reference vaccine. Subjects in recombinant rabies G protein vaccine arm received three doses of vaccine on days 0, 3, and 7, while subjects in reference vaccine arm received five doses of WHO prequalified vaccine on days 0, 3, 7, 14, and 28. Results: The socio-demographic characteristics of the two arms were comparable. About 9.9% subjects in recombinant rabies G protein vaccine arm and 17.2% subjects in reference arm reported adverse events. The sero-protection on day 14 was found to be 99.24% and 97.72% in recombinant rabies G protein vaccine arm and reference vaccine arm respectively and the difference was statistically nonsignificant. Conclusion: The novel three-dose recombinant rabies G protein vaccine administered as simulated postexposure prophylaxis was noninferior to five dose WHO prequalified vaccine in terms of safety and immunogenicity.